Analysis of Palm Sugar Production and Marketing from Nagari Talang Anau, Gunung Omeh District, 50 Kota Regency - Yusri Usman; Yusmarni Yusmarni (Journal of Social Research, 2023)
The research was carried out with the assistance of the Basic Research Scheme Batch 1 of Andalas University for Fiscal Year 2023. This study aims to describe palm sugar production, analyze the income and profit of palm sugar farmers, and analyze palm sugar marketing. This study used a survey method by sampling 35 palm sugar entrepreneur farmers by census and 1 collecting trader, 2 inter-regional traders and 10 retail traders who market palm sugar from farmers from Nagari Talang Anau, Gunung Omeh District, 50 City Regency. From the results of the study, it was found that palm sugar is made from palm sap which is traditionally tapped from male flower bunches of palm trees, then processed into palm sugar. The production process starts from tapping palm sap as raw material for palm sugar, cooking palm sap into palm sugar, printing and wrapping sugar and palm sugar ready to be marketed. The total production of palm sugar from Nagari Talang Anau is 1,285kg/week with an average of 36.54kg/farmer. The selling price of farmers is IDR 20,000/kg, production costs are IDR 7,734.67/kg with an average profit of IDR 12,263.33/kg. The return cost ratio (RCR) value of 2.59 which means that Rp 1.00 of cost sacrificed will result in a profit of Rp 1.59. There are 3 types of marketing channels, namely 1à) farmers, merchantsà, consumer retailers, 2) farmers, collecting traders, consumer retailers, and 3) farmersà, interregional tradersà, consumer à retailers à , where the à à most production is marketed outside the region through marketing channels 3 at 62.65%. Marketing channel 1 is sold to consumers of Gunung Omeh sub-district at a consumer price of IDR 22,000/kg, marketing channel 2 is sold to Payakumbuh City at a consumer price of IDR 25,000/kg and marketing channel 3 is sold to Riau Province with an average consumer price of IDR 26,000/kg. In marketing channel 1, farmers' profits are IDR 11,191.33/kg, retailers are 912.50/kg, in marketing channel 2 farmers' profits are IDR 12,749.66/kg, collecting traders IDR 1,010.91/kg and retailers are 2,111.05/kg. In marketing channel 3, farmers' profits are IDR 12,714.52/kg, interregional traders IDR 2,232.98/kg, retailers IDR 2,162.51/kg. Marketing efficiency based on cost was obtained in marketing channel 1 of 10.69, marketing channel 2 of 12.86 and marketing channel 3 of 11.48. Looks the 1st most efficient marketing channel. This palm sugar business provides high profits, especially to farmers. For this reason, it is recommended to increase the production and marketing of palm sugar.